Activity preferences and key competence in physical education - Julio Barrachina Peris (European Journal of Human Movement, 2022)
The aim of this study was to analyze the relationship between the variables of activity preferences in physical education lessons and their power of prediction on the development of basic competences. Based on the contextual isomorphism of teaching and learning situations in physical education, a scale of practice preferences was designed and validated and grouped into families, according to their construct and consequential validity. To do so, we designed and validated a scale of activity preferences in physical education lessons. Two studies were carried out with students between the ages of 12 and 18. The first study was on a sample of 219 participants, where an activity preferences scale was designed and validated. The second study was carried out on a sample of 476 students, and measured activity preferences and the perception of basic competences. The results showed that the activity preferences scale was valid and reliable. When class activities coincided with the students’ preferences it positively predicted basic competences.